2020
DOI: 10.1128/msystems.00724-20
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput RNA Sequencing Analysis of Plasma Samples Reveals Circulating microRNA Signatures with Biomarker Potential in Dengue Disease Progression

Abstract: The circulating microRNA (miRNA) profile has been widely used for identifying potential biomarkers against viral infections. However, data on circulating microRNA expression patterns in dengue patients are scanty. Considering the impact of severity caused by dengue infection, circulating miRNA profiles in plasma of dengue patients may prove to be valuable for developing early prognostic markers for the disease severity. Here, we described an in-depth analytical study of small RNA sequencing data obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…An essential component of reliable quantitative reverse transcription PCR (qRT-PCR) analyses is the normalization of gene expression data because it controls for variations and allows comparisons of gene expression levels among different samples. An ideal reference gene must be stably expressed, abundant and without any significant variation in its expression status 20 . Due to high heterogeneity, there is no consensus for the best reference gene to be used to normalize miRNA gene expression data in HO patients.…”
Section: Resultsmentioning
confidence: 99%
“…An essential component of reliable quantitative reverse transcription PCR (qRT-PCR) analyses is the normalization of gene expression data because it controls for variations and allows comparisons of gene expression levels among different samples. An ideal reference gene must be stably expressed, abundant and without any significant variation in its expression status 20 . Due to high heterogeneity, there is no consensus for the best reference gene to be used to normalize miRNA gene expression data in HO patients.…”
Section: Resultsmentioning
confidence: 99%
“…The study could successfully correlate the dysregulation of several miRNAs among mild and severe dengue patients. (Saini et al, 2020). Specifically, the expression profile of hsa-miR-122-5p in plasma specimens was found to be an important differentiator of dengue infection stage.…”
Section: Differentiation Of Mild Vs Severe Denguementioning
confidence: 91%
“…Leveraging the 'edge' R package in R software, we screened the differential expression of miRNAs in 12 miRNA-seq and TCGA database tissues. The screening criterion was log2(fold change) >1.5, and the cut-off for the false discovery rate (FDR) =0.05, there was statistical significance when P<0.05, in order to select the more significant differential miRNAs we referred to the literatures (13)(14)(15) and found that the difference was more significant when log2>1.5. With the help of the 'ggplot2' package in R software, two volcano maps of differentially-expressed miRNAs in the 12 miRNAseq and TCGA database tissues were drawn.…”
Section: Screening For Differential Mirna Expressionmentioning
confidence: 99%